A Possible Paleoindian/Early Archaic Point from Ladyville, Belize, Central America. (2nd January 2016) - James Stemp, W.; Awe, Jaime J.; Helmke, Chistophe G. B.
Abstract : A biface fragment (JuaD/98/12/1) was recovered in 1998 as a surface find near Ladyville in northern Belize, Central America. Based on morphological and technological criteria, this biface is most likely preceramic and might date to the Late Paleoindian/Early Archaic period (ca. 10, 000–8, 000 cal yr BP). To distinguish this point fragment from the two lanceolate, Clovis-style bifaces from Ladyville, we have tentatively designated it Ladyville Wide Stemmed.